2007
DOI: 10.1111/j.1467-8276.2007.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between the Student‐Advisor Match and Early Career Research Productivity for Agricultural and Resource Economics Ph.D.s

Abstract: We use a unique data set on students receiving their Ph.D.s from top-ranked agricultural and resource economics programs to investigate how the ranking of a student's dissertation advisor affects his or her early career research productivity. After controlling for program reputation, we find that the higher the relative research productivity of a student's dissertation advisor the greater the student's early career research productivity. Allowing the estimated effects of advisor rank to vary with program reput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 20 publications
2
32
0
1
Order By: Relevance
“…According to Fischer and Zigmond (1998), selection of an advisor constitutes one of the first and most significant decisions a graduate student makes. Other researchers have also found that the ability to select an advisor can significantly affect the quality of an advisor-advisee relationship (Hilmer & Hilmer, 2007;Lovitts, 2001;Schlosser et al, 2003). Because advisors play a significant role in the academic life and satisfaction of their advisees (see, e.g., Holland, 1998;Schlosser et al, 2003), the inability to choose an advisor upon matricula tion into an education program may contribute to the attrition rate.…”
Section: Discussionmentioning
confidence: 99%
“…According to Fischer and Zigmond (1998), selection of an advisor constitutes one of the first and most significant decisions a graduate student makes. Other researchers have also found that the ability to select an advisor can significantly affect the quality of an advisor-advisee relationship (Hilmer & Hilmer, 2007;Lovitts, 2001;Schlosser et al, 2003). Because advisors play a significant role in the academic life and satisfaction of their advisees (see, e.g., Holland, 1998;Schlosser et al, 2003), the inability to choose an advisor upon matricula tion into an education program may contribute to the attrition rate.…”
Section: Discussionmentioning
confidence: 99%
“…Determinants considered include age (see Goodwin and Sauer, 1995;Rauber and Ursprung, 2008), gender (see Davis and Patterson, 2001;Fabel et al, 2008), nationality (Mamiseishvili and Rosser, 2010); field of study (see Davis and Patterson, 2001), coauthorships (see Davis and Patterson, 2001;Hollis, 2001), conference attendance (see Prpić, 2000;, participation in PhD programs (see Austin, 2002;Bowen and Ruenstine, 1992;Sadowski et al, 2010;Schneider, 2010), participation in mentoring programs (see Gardiner et al, 2007;Muschallik and Pull, 2015), affiliation with research centers (Sabharwal and Hu, 2013), reputation and quality of department or university (see Allison and Long, 1990;Bedeian et al, 2010;Crane, 1965Crane, , 1970Long, 1978;Long and McGinnis, 1981;Long et al, 1998), department size (see Fabel et al, 2008;Golden and Carstensen, 1992;Turner and Mairesse, 2003), publication output of academic advisor (see Hilmer and Hilmer, 2007;Reskin, 1979;Williamson and Cable, 2003), and teaching load and service tasks (see Taylor et al, 2006). Some papers study the effect of mobility across countries on research productivity (e.g.…”
Section: Related Literaturementioning
confidence: 99%
“…Statistical analyses are yet to be done. This would make it possible to integrate control variables, such as the goal orientation of departments (Breneman 1976;Bartelse 1999;Sadowski et al 2008), the didactic elements of PhD education (Bowen and Rudenstine 1992;Hilmer and Hilmer 2007) or differing resource levels (Schneider et al 2009) and the interaction of these variables.…”
Section: Limitations and Outlookmentioning
confidence: 99%
“…One common measure is the publication record of PhD graduates (Hilmer and Hilmer 2007) or professors (Rauber and Ursprung 2008), but the total number of graduates (Leszczensky and Orr 2004) or the reputation of a graduate school (Ehrenberg 2004;Burris 2004) also serve as indicators for success. Yet these criteria suffer from pitfalls.…”
Section: Conditionsmentioning
confidence: 99%